A Role for Katanin-mediated Axonemal Severing during Chlamydomonas Deflagellation - Lohret, Timothy A. (The American Society for Cell Biology, 1998)
Deflagellation of Chlamydomonas reinhardtii, and other flagellated and ciliated cells, is a highly specific process that involves signal-induced severing of the outer doublet microtubules at a precise site in the transition region between the axoneme and basal body. Although the machinery of deflagellation is activated by Ca(2+), the mechanism of microtubule severing is unknown. Severing of singlet microtubules has been observed in vitro to be catalyzed by katanin, a heterodimeric adenosine triphosphatase that can remove tubulin subunits from the walls of stable microtubules. We found that purified katanin induced an ATP-dependent severing of the Chlamydomonas axoneme. Using Western blot analysis and indirect immunofluorescence, we demonstrate that Chlamydomonas expresses a protein that is recognized by an anti-human katanin antibody and that this protein is localized, at least in part, to the basal body complex. Using an in vitro severing assay, we show that the protein(s) responsible for Ca(2+)-activated outer doublet severing purify with the flagellar-basal body complex. Furthermore, deflagellation of purified flagellar-basal body complexes is significantly blocked by the anti-katanin antibody. Taken together, these data suggest that a katanin-like mechanism may mediate the severing of the outer doublet microtubules during Chlamydomonas deflagellation.